The single dad's Christmas proposal - Hayes, Ella (Harlequin romance, 2021)
"Extreme snowboarder Dax is no stranger to a challenge. Still, nothing could have prepared him for his greatest challenge yet: fatherhood! Six-year-old Yann was kept a secret by his late mother. Now Dax is determined to make up for lost time. But with a work commitment in Chamonix, he needs a step-in nanny and single mom Simone is the perfect candidate! Will Simone say yes to Dax- and a Christmas to remember?" --Back cover.